1999
DOI: 10.1002/(sici)1097-0177(199912)216:4/5<336::aid-dvdy3>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific homeotic vertebral transformations in mouse fetuses induced by maternal hyperthermia during somitogenesis

Abstract: To investigate the heat shock effects upon somitogenesis and specification of the vertebral identity, pregnant ICR mice were briefly exposed to 42°C or 43°C at E7.5, E8.5, or E9.5 (noon of the plug day = E0.5). Heat treatment induced embryonic day‐specific vertebral transformations whose frequency and severity were dependent on the temperature elevation. Following a heat treatment at E8.5, the vertebral identity of T6 through S1 was shifted anteriorly by one or two segments (posterior transformations). Such sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…7a). In agreement with this, HS in mice and rats inhibits cell proliferation, leading to vertebral deformity (Breen et al 1999;Li and Shiota 1999). In mice, more than 4,000 genes are transcriptionally altered after HS, indicating that our study of two genes reflects "a short chapter" of the whole story (Mikheeva et al 2004).…”
Section: Discussionsupporting
confidence: 79%
“…7a). In agreement with this, HS in mice and rats inhibits cell proliferation, leading to vertebral deformity (Breen et al 1999;Li and Shiota 1999). In mice, more than 4,000 genes are transcriptionally altered after HS, indicating that our study of two genes reflects "a short chapter" of the whole story (Mikheeva et al 2004).…”
Section: Discussionsupporting
confidence: 79%
“…Recent studies have shown that the genetic diversity was extremely low in Late Pleistocene mammoth populations in Siberia (Miller et al, 2008; Nyström et al, 2012). Additionally, the increased incidence of cervical ribs may be due to harsh conditions that impact early pregnancies, because diseases, famine, cold and other stressors can lead to disturbances of early organogenesis, that can result in the induction of cervical ribs (e.g., Sawin, 1937; Li & Shiota, 2000; Wéry et al, 2003; Chernoff & Rogers, 2004; Steigenga et al, 2006). Harsh conditions during the Late Pleistocene, a period of intense climatic fluctuations and ecosystem instability, are plausible (Brace et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the extreme evolutionary conservation of the number of cervical vertebrae, intraspecific variation is not uncommon in mammals. The most common variation is represented by ribs on the seventh vertebra, so-called cervical ribs, which can be considered a partial or complete homeotic transformation of a cervical into a thoracic vertebra (involving a change in the activity of Hox genes (Galis, 1999; Li & Shiota, 2000; Varela-Lasheras et al, 2011; Wéry et al, 2003)). The strong conservation of the number of cervical vertebrae implies that there must be selection against intraspecific variation of this number.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat shocks were proposed to affect somite delimitation by the 'prior wave'. Disruption of somitogenesis by heat shocks is a phenomenon shared (with some differences) across species; the first defects occur after 6-7 somites in chick , 4-5 somites in zebrafish (Roy et al, 1999), 4 somites in rats (Cuff et al, 1993), but less than 2 somites in mouse (Li and Shiota, 1999).…”
Section: Determination Frontmentioning
confidence: 99%